2021
DOI: 10.1155/2021/7061623
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality as Pedagogical Tool to Enhance Experiential Learning: A Systematic Literature Review

Abstract: Since half of the century, technology has dominated the modern era. The rapid advancement of technology has reached generating artificial intelligence and artificial realities. So, virtual reality is an emerging technology and is applicable in education as well. Virtual reality is a computer-generated simulation, where people can interact within an artificial environment. Moreover, in an educational setting, such an environment provides students with a chance to get experiential learning. This paper has a syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(32 citation statements)
references
References 79 publications
(104 reference statements)
3
29
0
Order By: Relevance
“…Also, the participants Education Research International considered the immersive nature of virtual reality, which can help enhance experiential learning among students. Thus, it concludes that the perceptions of undergraduate students are aligned with literature that supports the idea of virtual reality that works as a pedagogical tool and helps in promoting the experiential learning of students [10,34].…”
Section: Ethical Considerationssupporting
confidence: 52%
See 2 more Smart Citations
“…Also, the participants Education Research International considered the immersive nature of virtual reality, which can help enhance experiential learning among students. Thus, it concludes that the perceptions of undergraduate students are aligned with literature that supports the idea of virtual reality that works as a pedagogical tool and helps in promoting the experiential learning of students [10,34].…”
Section: Ethical Considerationssupporting
confidence: 52%
“…Thus, this study is aimed at exploring the effect of virtual reality as a pedagogical tool for enhancing experiential learning among undergraduate students of the education department (pre-service teachers). Recently, exclusive literature related to virtual reality for enhancing students' experiential learning has found that virtual reality aids students' experiential learning by allowing them to interact and immerse in a provided simulated environment [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Virtual reality (VR) has a high potential for teaching in different domains, like engineering [2], [6], because it enriches learning environments [20]. The use of VR could enhance experimental learning [21]. With interdisciplinary stakeholders in our projects, we designed a system to simplify the xAPI tracking setup, according to iterative design and design-based research [22].…”
Section: Fig 3 Example Basket: a Collection Of Remote Lab Definitionsmentioning
confidence: 99%
“…Businesses and organizations are forced to re-think and re-envision their operational processes, customer experience, and business models leading to digital transformation (Westerman et al, 2011). Digital transformation involves "a progressive re-thinking of the use of advanced technologies and the ways to use technology to bring about progress in people's lives and processes" (Asad et al, 2021).…”
Section: Introductionmentioning
confidence: 99%